CARBONIZATION OF BANTEN COAL BY ADDING WATER STEAM; CHANGES ON CARBON FUNCTIONAL GROUPS AND PORE CHARACTERISTICS - Anggoro T. Mursito; Atet Saepuloh; Eki N. Dida (Indonesian Mining Journal, 2014)
Experimental research and a fundamental study of carbonization of coal have been done by adding steam. The coal sample used in this study was obtained from Bayah, Banten, where the coal was mined by a small-scale underground mining. The study was carried out on a laboratory-scale of adjustable tube furnace reactor. The processes could give carbonized coal with a high calorific value (about 7,600 kcal/kg) and a high fixed carbon content (about 87 wt%). Specific surface area of carbonized products was also interesting as having for 160.5 m2/g. Specific surface area and pore distribution determined by BET techniques and also scanning electron microscope analyses were used to test for the pore and physical properties in the coal. In addition, changes in carbon functional groups and their properties were determined by Fourier Transform Infrared Spectroscopy and Raman Spectroscopy analysis of the products, upgrading process and maturation analyses.